1973
DOI: 10.1159/000124424
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal Fibers to the Retina in the Rhesus Monkey

Abstract: In addition to the retinofugal fibers from theganglion cells of the retina and the supraoptic commissural fibers (Gudden''s commissure), the optic tracts, chiasm, and nerves of the rhesus monkey contain centrifugal (retinopetal, optic efferent) fibers to the retina. The centrifugal fibers were identified in the optic nerves, chiasm, and tracts of bilaterally enucleated monkeys on the basis of the principle that, following enucleation, the retinofugal fibers within the optic nerves, chiasm, and tracts degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We cannot exclude the possibility that some GABA + fibers in the NFL are efferents. In primate retina, efferents have been reported in studies using reduced silver (Wolter, 1957(Wolter, , 1965Honrubia & Elliott, 1968, 1970Noback & Mettler, 1973;Reperant et al, 1981) and more definitively, HRP uptake from optic nerve injections (Perry et al, 1984), but these efferent axons all terminated in the INL or the IPL. We saw no indication of long GABA + fibers with terminal arborizations in the NFL.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that some GABA + fibers in the NFL are efferents. In primate retina, efferents have been reported in studies using reduced silver (Wolter, 1957(Wolter, , 1965Honrubia & Elliott, 1968, 1970Noback & Mettler, 1973;Reperant et al, 1981) and more definitively, HRP uptake from optic nerve injections (Perry et al, 1984), but these efferent axons all terminated in the INL or the IPL. We saw no indication of long GABA + fibers with terminal arborizations in the NFL.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of eye position is likely to be mediated by descending feedback connections. As descending connections affect the very earliest possible levels of auditory processing (for reviews, see Giard et al 2000;Simmons 2002) and also reach the retina (Brooke et al 1965;Labandeira-Garcia et al 1990;Noback and Mettler 1973), we may be only scratching the surface of eye-position effects in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Many anatomical studies have suggested the presence of centrifugal fibers in the optic nerve and retina in mammals, including humans (see Stell, 1972;Rodieck, 1973;Noback & Mettler, 1973;Wakakura & Ishikawa, 1982 for review). Although much of this evidence seems inadequate to prove the presence of the retinopetal system (see Brindley & Hamasaki, 1966), evidence obtained by silver-impregnation methods strongly suggests centrifugal fibers in the mammalian retina (e.g.…”
Section: Centrifugal Fibers In the Mammalian Retina: Anatomical And Pmentioning
confidence: 99%